2020
DOI: 10.1515/aot-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Materials for D-D-A ternary organic solar cells: an absorption model study

Abstract: AbstractHeterojunction solar cells based on ternary blends of two donors (absorbers and one acceptor) were investigated using modeling. The Tauc-Lorentz model and experimental absorption spectra of selected compounds were used in the simulations. The optimization process was carried out in this way to maximize the absorption of the system. Poly(3-hexylthiophene-2,5-diyl) (PEHT) was investigated as a first donor, which was mixed respectively with poly(3-octylthiophene-2,5-diyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Comprehensive studies were carried out in terms of the selection of polymer matrix, compatibility, and properties of composites as a whole. The drying process of the perovskite solution could lead to composite surface defects due to its complex hydrodynamics [ 49 , 50 , 51 ]. In previous studies, PEO was suggested as a potential matrix to improve the film and device quality in perovskite-based composites [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive studies were carried out in terms of the selection of polymer matrix, compatibility, and properties of composites as a whole. The drying process of the perovskite solution could lead to composite surface defects due to its complex hydrodynamics [ 49 , 50 , 51 ]. In previous studies, PEO was suggested as a potential matrix to improve the film and device quality in perovskite-based composites [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%